Units, symbols, and terminology for plant physiology - Salisbury, Frank B. (Oxford University Press, 1996)
This book represents a beginning toward a consensus on units, symbols, and terminology in the plant sciences. Written by 27 specialists and reviewed by several others, each discussion is condensed for easy reference, but still thorough enough to answer virtually any question concerning plant terminology. Principles are outlined and covered in readable text. Some chapters include formulas and definitions of specialized terms, while others include recommendations for suitable units. The appendices offer guidelines on presenting scientific data, such as principles of grammar, oral and poster presentations, and reporting on data from experiments that utilized growth chambers. Anyone involved in the plant sciences, particularly plant physiology, will find this an invaluable reference